If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.33(6 + x) + -5 = 12 (6 * 0.33 + x * 0.33) + -5 = 12 (1.98 + 0.33x) + -5 = 12 Reorder the terms: 1.98 + -5 + 0.33x = 12 Combine like terms: 1.98 + -5 = -3.02 -3.02 + 0.33x = 12 Solving -3.02 + 0.33x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3.02' to each side of the equation. -3.02 + 3.02 + 0.33x = 12 + 3.02 Combine like terms: -3.02 + 3.02 = 0.00 0.00 + 0.33x = 12 + 3.02 0.33x = 12 + 3.02 Combine like terms: 12 + 3.02 = 15.02 0.33x = 15.02 Divide each side by '0.33'. x = 45.51515152 Simplifying x = 45.51515152
| -(v+x)+6(-4x+4v)= | | 3t^2=75 | | 72=3w | | -(-5-2f)-(8-3f)=22 | | 36x^2-63x+20=0 | | -(-5f)-(8-3f)=22 | | -(-8-2f)-(8-3f)=22 | | (-4e+9)-(3e+2)=0 | | 4d-5=d+7 | | 4b-5=3b+3 | | 2x^2=512 | | v^2+v-30=0 | | 10a+12=5a+32 | | 6.00+3.50(x+1)=44.50 | | 65+195(x+1)=2405 | | 2x-4=8x+7 | | 2x(4-7)=6x(3-9) | | 2x-4=8x+7x | | 7+1x=40 | | 42t^2-17t=15 | | -4x-[3x-2(x+6)]-7= | | 12r^2-13r=35 | | -4x-3[3x-3(x+6)]-5= | | 9x-(6x+4)= | | 16=c(c-6) | | -6x+4[x-6(2-x)]= | | -8.1+5x-6.1+2x-2.5=5.8+8x+1.4 | | -2[3x-(x+8)]= | | -4[x+2(6-x)]= | | 6w^2-11w=35 | | 9x^2-45x+54=0 | | 31.00+1.00x=65 |